Micellization and colloidal adsorption of a model polyelectrolyte diblock copolymer in selective solvent: theoretical model combining scaling and lattice mean field approaches - Natarajan, Upendra; Poddar, Neha (231st National Meeting of the American-Chemical-Society, 2006)
231st National Meeting of the American-Chemical-Society, Atlanta, GA, MAR 26-30, 2006

Preparation and characterization of a series of new organically modified montmorillonite clays using X-ray diffraction, thermogravimetric analysis and FTIR spectroscopy - Natarajan, Upendra; Tiwari, Rajkiran R. (231st National Meeting of the American-Chemical-Society, 2006)
231st National Meeting of the American-Chemical-Society, Atlanta, GA, MAR 26-30, 2006

Influence of organic modification on mechanical properties of melt processed intercalated poly(methyl methacrylate)-organoclay nanocomposites - Tiwari, Rajkiran R.; Natarajan, Upendra (Journal of Applied Polymer Science, 2007)
The influence of organic modifiers on intercalation extent, structure, thermal and mechanical properties of poly(methyl methacrylate) (PMMA)-clay nanocomposites were studied. Two different organic modifiers with varying hydrophobicity (single tallow versus ditallow) were investigated. The nanocomposites were prepared from melt processing method and characterized using wide angle X-ray diffraction, transmission electron microscopy, thermogravimetric analysis, differential scanning calorimetry (DSC), and tensile tests. Mechanical properties such as tensile modulus (E), break stress (sigma(brk)), and 0% break strain (epsilon(brk)) were determined for nanocomposites at various clay loadings. Extent of PMMA intercalation is sufficient and in the range 9-15 angstrom depending on organoclay and filler loading. Overall thermal stability of nanocomposites increases by 16-30 degrees C. The enhancement in T-g of nanocomposite is merely by 2-4 degrees C. With increase in clay loading, tensile modulus increases linearly while % break strain decreases. Break stress is found to increase till 4 wt % and further decreases at higher clay loadings. The overall improvement in thermal and mechanical properties was higher for the organoclay containing organic modifier with lower hydrophobicity and single tallow amine chemical structure. (c) 2007 Wiley Periodicals, Inc.
Keywords: mechanical properties; Nanocomposites; organoclay; structure; Thermal properties

Effect of organic modifiers and silicate type on filler dispersion, thermal, and mechanical properties of ABS-Clay nanocomposites - Tiwari, Rajkiran R.; Natarajan, Upendra (Journal of Applied Polymer Science, 2008)
Acrylonitrile-butadiene-styrene (ABS)-clay composite and intercalated nanocomposites were prepared by melt processing, using Na-montmorillonite (MMT), several chemically different organically modified MMT (OMMT) and Na-laponite clays. The polymer-clay hybrids were characterized by WAXD, TEM, DSC, TGA, tensile, and impact tests. Intercalated nanocomposites are formed with organoclays, a composite is obtained with unmodified MMT, and the nanocomposite based on synthetic laponite is almost exfoliated. An unintercalated nanocomposite is formed by one of the organically modified clays, with similar overall stack dispersion as compared to the intercalated nanocomposites. T, of ABS is unaffected by incorporation of the silicate filler in its matrix upto 4 wt % loading for different aspect ratios and organic modifications. A significant improvement in the onset of thermal decomposition (40-44 degrees C at 4 wt % organoclay) is seen. The Young's modulus shows improvement, the elongation-at-break shows reduction, and the tensile strength shows improvement. Notched and unnotched impact strength of the intercalated MMT nanocomposites is lower as compared to that of ABS matrix. However, laponite and overexchanged organomontmorillonite clay lead to improvement in ductility. For the MMT clays, the Young's modulus (E) correlates with the intercalation change in organoclay interlayer separation (Delta d(001)) as influenced by the chemistry of the modifier. Although ABS-laponite composites are exfoliated, the intercalated OMMT-based nanocomposites show greater improvement in modulus. (C) 2008 Wiley Periodicals, Inc. J Appl Polym Sci 110:2374-2383, 2008
Keywords: clay; filler; mechanical; structure characterization; styrene-butadiene

Monte carlo simulations of chain dimensions and conformational properties of various poly(n-alkyl methacrylates) in solution - Karyappa, Rahul B.; Natarajan, Upendra (Journal of Macromolecular Science Part B-Physics, 2008)
Rotational Isomeric State (RIS) Metropolis Monte Carlo (RMMC) simulations of the conformational properties and chain dimensions of a series of chemically different poly(n-alkyl methacrylates) including poly(methyl methacrylate), poly(n-butyl methacrylate), poly(n-hexyl methacrylate), and poly(phenyl methacrylate), in the theta state were investigated, and (r(2)/M)(1/2), (s(2)/M)(1/2) and C(n) were calculated and compared in order to obtain fundamental understanding of the influence of the chemical structure. Simulations were conducted for different molecular weights. Results obtained from the simulations are compared with experimentally obtained dimensions in the literature using the Mark-Houwink relationship as well as, in some cases, data available from direct determinations in theta solvents. Good agreement between simulation and experimental data was obtained. The backbone conformation is predominantly trans in these polymers. Increase in bulkiness and rigidity of the substituting acrylate side group results in an increase in trans and a decrease in gauche backbone conformer population. In the case of rotatable bonds in the side-group structure, increase in rigidity of the side group leads to a decrease in the trans population, although this effect is not uniformly observed.
Keywords: chain dimensions; Monte Carlo simulation; polymethacrylate; theta solvent

New poly(phenylene oxide)/polystyrene blend nanocomposites with clay: intercalation, thermal and mechanical properties - Tiwari, Rajkiran R.; Khilar, Kartic C.; Natarajan, Upendra (Journal of Applied Polymer Science, 2008)
We present the first study and results on the preparation and characterization of montmorillonite clay filter based polymer blend nanocomposites of the miscible poly(phenylene oxide)/polystyrene blend. Intercalated nanocomposites, prepared by a melt-processing method with 2-6 wt % commercially available organically modified sodium montmorillonite, have been characterized with wide-angle X-ray diffraction, transmission electron microscopy analysis, thermal analysis (thermogravimetric analysis and differential scanning calorimetry), and mechanical tensile tests. We show that nanocomposites can be successfully prepared in a batch mixer at temperatures much below the conditions conventionally used for this blend without organic degradation. Thermal stability is enhanced by nanoscale hybrid formation. The level of intercalation (change in the d-spacing) does not change with the clay loading. Better dispersion of clay in the blend matrix has been observed at a low level of clay content. The nanocomposites show improved tensile modulus (by 31%) in comparison to the blend, whereas the tensile strength (stress at break) and elongation decrease in the presence of the filler with an increase in the clay loading. The Halpin-Tsai model is able to predict the modulus of the nanocomposites in very good agreement with the experimental data. (c) 2008 Wiley Periodicals, Inc.
Keywords: mechanical properties; Nanocomposites; organoclay; poly(phenylene oxide); Polystyrene; Thermal properties

Synthesis and characterization of novel organo-montmorillonites - Tiwari, Rajkiran R.; Khilar, Kartic C.; Natarajan, Upendra (Applied Clay Science, 2008)
Sodium Montmorillonite (NaMMT) has been modified via cation exchange reaction using three different organic cations. Basal spacings, interlamellar structure and thermal stability of these organo-montmorillonites (OMMT) clays have been characterized using wide angle X-ray diffraction (WARD) and thermogravimetric analysis (TGA) techniques. Increase in the basal spacing due to organic modification is in good agreement with simple theoretical calculations based on van der Waals volume of the cationic ammonium ions. TGA characterization and analysis show that the amount of organic modifier in the OMMT's is in good agreement with theoretically calculated stoichiometric content expected for almost complete exchange of Na+ ions by organic cations. The OMMT's shows stepwise decomposition corresponding to initial weight loss from residual water desorption, followed by decomposition of the organic surfactant and the dehydroxylation of structural water of the montmorillonite layers. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Montmorillonite; organo-clays; organo-montmorillonite; surfactant

Thermal and mechanical properties of melt processed intercalated poly(methyl methacrylate)-organoclay nanocomposites over a wide range of filler loading - Tiwari, Rajkiran R.; Natarajan, Upendra (Polymer International, 2008)
BACKGROUND: Poly(methyl methacrylate) (PMMA)-organoclay nanocomposites with octadecylammonium, ion-modified montmorillonite, prepared via melt processing, over a wide range of filler loading (2-16 wt%) were investigated in detail. These hybrids were characterized for their dispersion structure, and thermal and mechanical properties, such as tensile modulus (E). break stress (sigma(brk)), percent break strain (epsilon(brk)) and ductility(J), using wide-angle X-ray diffraction, transmission electron microscopy, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and tensile and impact tests. RESULTS: Intercalated nanocomposites were formed even in the presence of 16 wt% clay (high loading) in PMMA matrix. PMMA intercalated into the galleries of the organically modified clay, with a change in d-spacing in the range 11-16 angstrom. TGA results showed improved thermal stability of the nanocomposites. The glass transition temperature (T-g) of the nanocomposites, from DSC measurements, was 2-3 degrees C higher than that of PMMA. The ultimate tensile strength and impact strength decreased with increasing clay fraction. Tensile modulus for the nanocomposites increased by a significant amount (113%) at the highest level of clay fraction (16 wt%) studied. CONCLUSION: We show for the first time the formation of intercalated PMMA nanocomposites with alkylammonium-modified clays at high clay loadings (> 15wt%). Tensile modulus increases linearly with clay fraction, and the enhancement in modulus is significant. A linear correlation between tensile strength and strainat-break is shown. Thermal properties are not affected appreciably. Organoclay can be dispersed well even at high clay fractions to form nanocomposites with superior bulk properties of practical interest. (c) 2007 Society of Chemical Industry.
Keywords: impact strength; mechanical properties; Nanocomposites; PMMA; Thermal properties

Effect of blend composition and organoclay loading on the nanocomposite structure and properties of miscible poly(methyl methacrylate)/poly(styrene-co-acrylonitrile) blends - Tiwari, Rajkiran R.; Natarajan, Upendra (Polymer Engineering and Science, 2011)
Organically-modified montmorillonite clay nanocomposites of poly(styrene-co-acrylonitrile) (SAN), poly(methyl methacrylate) (PMMA) and SAN/PMMA miscible blend are investigated. Structure characteristics at the nanoscale and microscale and thermal and tensile properties are studied as a function of polymer blend composition and filler loading fraction. Blend miscibility and T(g) are unaffected by up to 10% by wt. organoclay. Thermal degradation stability increases with SAN content and exhibits an optimum value of clay loading. Stiffness shows significant improvement. Tensile strength and elongation-at-break suffer as a result of nanocomposite formation. Modulus shows a maximum enhancement of 57% (5 +/- 0.06 GPa at 10 wt% filler, 20/80 SAN/PMMA) and varies linearly with clay fraction for all compositions of matrix phase. Predictions of Halpin-Tsai composite model are in excellent agreement with the experimental behavior over full range of polymer blend composition. Fundamental aspects of a polymer blend-clay nanocomposite are clarified, such as lack of additional synergy between clay platelets and matrix, and tensile ductility reduction, compared with polymer-clay system. POLYM. ENG. SCI., 51:979-991, 2011. (C) 2011 Society of Plastics Engineers

Effect of chemical substituents on the structure of glassy diphenyl polycarbonates - Sulatha, M. S.; Natarajan, Upendra (Journal of Physical Chemistry B, 2011)
Polycarbonates offer a wide variety of physical property behavior that is difficult to predict due to complexities at the molecular scale. Here, the physical structure of amorphous glassy polycarbonates having aliphatic and cycloaliphatic chemical groups is explored through atomistic simulations. The influence of chemical structure on solubility parameter, torsion distributions, radial distribution function, scattering structure factor; orientation distributions of phenylene rings and carbonate groups, and free volume distributions, leading to interchain packing effects, are shown. The effect of the cyclohexyl ring at the isopropylidene carbon as compared to the effect of the methyl groups positioned on the phenylene rings results in a larger reduction in the solubility parameter (delta). The interchain distance estimated for polycarbonates in this work is in the range of 5-5.8 angstrom. The o-methyl groups on the phenylene, rings, as compared to a cyclohexyl ring, lead to higher interchain distances. The highest interchain distance is observed with a trimethylcyclohexylidene group at the isopropylidene carbon. Atomistic simulations reveal two different types of packing arrangement of nearest neighbor chains in the glassy state, one type of which agrees with the NMR experimental data The fundamental insights provided here can be utilized for design of chemical structures for tailored macroscopic properties.

Effect of composition on chain dimensions of styrene-methylmethacrylate random copolymers under theta condition - Karyappa, Rahul B.; Natarajan, Upendra (Journal of Macromolecular Science Part B-Physics, 2011)
Rotational-isomeric-state (RIS)-Metropolis Monte Carlo simulations are performed on poly(styrene-ran-methylmethacrylate) random copolymers to study the intrinsic unperturbed (theta-condition) dimensions. Mean-squared end-to-end distance (< r(2)>(o)), mean-squared radius of gyration (< s(2)>(o)), and characteristic ratio (C(n)) have been calculated for these copolymers constituted by different overall chemical compositions (styrene fractions 0.29, 0.56, and 0.70). Calculations were carried out with chains of 500 repeating units. With an increase in the styrene content there is an increase in (< r(2)>(o)), `, and C(n), in agreement with experimental observations. An increase in the fraction of trans conformational states in the backbone torsion angles is found to be responsible for the exhibited chain expansion behavior. The dimensions calculated by the Monte Carlo simulations agree well with experimental values reported in the literature.
Keywords: chain dimensions; Monte Carlo; poly(methyl methacrylate); Polystyrene; random copolymer; theta conditions

Molecular simulations of the conformational properties of atactic poly(2-ethylbutyl methacrylate) - Karyappa, Rahul B.; Natarajan, Upendra (Journal of Applied Polymer Science, 2012)
RIS Metropolis Monte Carlo (RMMC) simulations were used to determine the unperturbed theta-state chain dimensions of atactic stereoconfigurations of poly (2-ethylbutyl methacrylate) [PEBMA]. Root mean-squared end-to-end distance (< r(2)>(o)/M)(1/2) and characteristic ratio (Cn) were calculated along with the backbone torsion angle distribution. The simulated properties are in very good agreement with experimental results. The values of the PEBMA chain dimensions are in-between those corresponding ones for poly(n-butyl methacrylate) and poly (n-hexyl methacrylate) thereby showing the effect of branching in the side-chain. (c) 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: chain dimensions; conformations; Monte Carlo simulation; poly(2-ethylbutyl methacrylate); vinyl polymer

Prediction of structure and energy of trans-1,4-polybutadiene glassy surface by atomistic simulations of free-standing ultrathin films - Ijantkar, Ashwini S.; Natarajan, Upendra (Journal of Macromolecular Science Part B-Physics, 2012)
Atomistic modeling of amorphous trans-1,4-polybutadiene (TPBD), using molecular mechanics and molecular dynamics (MD) simulations, is performed to generate three-dimensionally periodic bulk and two-dimensionally periodic thin film condensed phases. The condensed structures are constructed using multiple polymer chains. Structural and energetic relaxations and sampling of properties are performed using MD in the canonical ensemble (NVT) by a procedure that relieves local high-energy spots and brings the system to realistic thermodynamic states. The calculated surface energy for TPBD, 30.72 erg/cm(2), is in excellent agreement with the reported experimental value of 31 erg/cm(2). The structure of the surface layers is probed in terms of the atomic mass density variations, bond-bond orientation function profiles, and the distribution of the dihedral angles about the rotatable backbone bonds. The thickness of the surface layer over which the density varies smoothly but rapidly is found to be approximately 15 angstrom. The level of agreement of the calculated surface energy with the experimental value is superior in comparison to previous investigations in the literature using the atomistic approach for flexible polymers.
Keywords: 4-polybutadiene; atomistic simulation; bond-orientation; Conformation; molecular dynamics; polymer glass; surface energy; trans-1

Effect of organic modification on the intercalation and the properties of poly(phenylene oxide)/polystyrene blend-clay nanocomposites - Tiwari, Rajkiran R.; Natarajan, Upendra (Journal of Thermoplastic Composite Materials, 2013)
Nanocomposites prepared by the dispersion of unmodified and organically modified montmorillonite (MMT) clay into poly(2,6-dimethyl phenylene oxide)/polystyrene miscible blend in the range of 2-10 wt% clay were investigated by wide-angle x-ray diffraction, transmission electron microscopy, differential scanning calorimetry, thermogravimetric analysis and tensile mechanical tests. The systems based on unmodified sodium MMT (Na+MMT) as well as Cloisite 20A, Cloisite 30B and Cloisite 10A organically modified clays showed polymer intercalation. The glass transition temperature (T-g) value was not affected by the volume fraction of clay and chemical nature of the organoclay. The thermal degradation stability of nanocomposites is found to be only slightly better than that of the blend matrix. A percolation threshold of around 4 wt% organoclay loading is observed. An improvement of 35% relative to unfilled polymer blend matrix is observed for the modulus, for Cloisite 20A nanocomposite containing 2 wt% organoclay. The observed modulus improvement with significant retention of elongational tensile strength and tensile ductility in case of unmodified Na-MMT and Cloisite 30B nanocomposites appears promising. The modulus prediction using Halpin-Tsai model is found to be closer to the experimental data when MMT volume fraction rather than the organoclay volume fraction is used.
Keywords: filler; interface; interphase; mechanical properties; Nanostructures; Polymer-matrix composites

Critical organic modifier aliphatic tail length for the formation of poly(methyl methacrylate)-montmorillonite nanocomposites - Tiwari, Rajkiran R.; Natarajan, Upendra (Polymer Engineering and Science, 2020)
In this article, we report the influence of organic modifier structure (alkyl chain length C8-C20, single vs ditallow) and thereby, the effect of hydrophobicity on the structure, thermal and mechanical properties of poly(methyl methacrylate) (PMMA)-clay hybrids. Melt processed PMMA-clay hybrids were characterized using wide-angle X-ray diffraction, transmission electron microscopy, and differential scanning calorimetry. The organoclays having an alkyl chain length of more than 12 CH2 groups resulted in the formation of nanocomposites. The glass transition temperature (T-g) of PMMA increased in the presence of clay. The mean-field lattice model was used to predict the free energy for nanocomposite formation, which showed a reasonable match with the experimental results and provided a general guideline for the proper selection of polymer and organoclay (ie, organic modifier) to obtain nanocomposite. Tensile modulus showed maximum improvement of 58% for the nanocomposites compared to 9% improvement for the composites. Tensile modulus increased with increases in the alkyl chain length of the organic modifier and clay loading. The level of improvement for the tensile properties of nanocomposites prepared from primary and secondary ammonium-modified clay is the same as that obtained with the commercial organoclays.
Keywords: hybrid; mechanical properties; Montmorillonite; Nanocomposites; organoclay; poly(methyl methacrylate)